Diagnosis and treatment of COVID–19 in primary healthcare - Punoševac, Darinka (General Practice, 2022)
COVID-19 pandemic is caused by the SARS-Cov-2virus and it was first isolated in Wuhan, China, in December2019. In Primary Healthcare Center (PHC), Krusevac,the outpatient clinic for respiratory infections was formed onMarch 24th, 2020. Nearly 100.000 medical exams were performedthere, up til now.The virus transmission is carried out by airborne droplets,or rarely using contaminated hands. The entrance site ofthe infection is nose, mouth, or eye mucose.The infection develops in two stages. The first happensin the upper respiratory tract (URT) and lasts 5-7 days, andthe second, when the virus descends to the lungs, and fromthere causes systemic inflammation, primarily of the bloodvessels.The diagnosis is based on the personal history, clinicalpresentation, physical exam, specific viral tests, lab analysis,and eventually, chest X-ray.Therapy is mainly symptomatic, and since March 2021we got antiviral favipiravir, and in January 2022 another antiviral,molnupiravir, became available. Oral corticosteroidsshowed promising results in patients with viral pneumonia.Primary healthcare was a dam against the secondaryand tertiary healthcare this time, too. As our colleaguesworldwide, we were learning in stride, and the process is ongoing.The more people get exposed to the virus, either naturallyor by vaccination, the sooner the pandemic will end butnot entirely and probably stay with us as a seasonal infectionwith easier clinical presentation.
Keywords: COVID-19; primary healthcare; treatment